Religion og mangfoldigheden af identiteter - Sökefeld, Martin (Religionsvidenskabeligt tidsskrift, 2002)
The conceptualization of identity proposed in this article is in terms of plurality, difference and intersectionality, which certainly disfavours essentialism. However, it highlights agency as the ability to act reflexively within settings of crosscutting identifications. This agency includes the ability to imagine and engage essentialised identities, momentarily dissimulating intersecting identifications. This article will stress that we have to conceptualize ‘identity’ in a way that is able to accomodate both the essentialisations of actors and the deconstruction of analysis.